The role of factor inhibiting HIF-1 in the cardiovascular responses to hypoxia - Platt, Simon (2022)
Many diseases of the cardiovascular system involve an element of hypoxia due to impairments in oxygen delivery. Central to the cellular responses to hypoxia is the hypoxia inducible factor (HIF) transcription factor signalling system. The HIF system is somewhat unique in that the labile α subunit is constantly expressed, but signalling constrained in an oxygen dependent manner by both prolyl hydroxylase domain (PHD) enzymes and an asparaginyl hydroxylase, factor inhibiting HIF1 (FIH1). PHD enzymes regulate the degradation of HIFα, whereas FIH1 inhibits co-factor binding needed to induce target gene expression, both in an oxygen dependent manner. This thesis aimed to understand the role of FIH1 in aspects of the cardiovascular responses to hypoxia.